2016
DOI: 10.1152/japplphysiol.01043.2015
|View full text |Cite
|
Sign up to set email alerts
|

Effect of betamethasone, surfactant, and positive end-expiratory pressures on lung aeration at birth in preterm rabbits

Abstract: Antenatal glucocorticoids, exogenous surfactant, and positive end-expiratory pressure (PEEP) ventilation are commonly provided to preterm infants to enhance respiratory function after birth. It is unclear how these treatments interact to improve the transition to air-breathing at birth. We investigated the relative contribution of antenatal betamethasone, prophylactic surfactant, and PEEP (3 cmHO) on functional residual capacity (FRC) and dynamic lung compliance (C) in preterm (28 day GA) rabbit kittens at bir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 53 publications
0
3
1
Order By: Relevance
“…While intratracheal surfactant application improves lung aeration as well as ventilation homogeneity,34 35 we did not see a meaningful effect of prophylactic SN on physiological outcomes. Any effects towards a different ventilation distribution were marginal and vanished after correction for multiple testing.…”
Section: Discussioncontrasting
confidence: 62%
“…While intratracheal surfactant application improves lung aeration as well as ventilation homogeneity,34 35 we did not see a meaningful effect of prophylactic SN on physiological outcomes. Any effects towards a different ventilation distribution were marginal and vanished after correction for multiple testing.…”
Section: Discussioncontrasting
confidence: 62%
“…Kittens were mechanically ventilated to avoid the variability associated with spontaneous breathing and to assess the effect of elevated airway liquid volumes on respiratory mechanics. Following imaging onset, ventilation commenced with intermittent positive pressure ventilation, commencing with a peak inflation pressure (PIP) of 25 cmH 2O, a positive end-expiratory pressure (PEEP) of 5 cmH2O, and inspiratory and expiratory times of 0.5 s. The PIP was increased to achieve a Vt of 8 ml/kg, which was measured directly from the plethysmograph, as previously described (5). During the ventilation period, following the initial 5-cmH 2O PEEP stage (5PEEP-I), the PEEP was decreased to 3 cmH2O (3PEEP) and then to 0 cmH2O (0PEEP) before it was returned to 5 cmH2O (5PEEP-F; Fig.…”
Section: Ventilation Protocolmentioning
confidence: 99%
“…Aeration of the gasless fluid-filled lung is the critical event at birth, triggering the rapid changes in the respiratory and vascular systems necessary to adapt to extrauterine life. Aeration is a complex process dependent on several factors, including developmental and disease state of the lung (15), spontaneous breathing activity (24), expiratory braking (24), effective lung fluid reabsorption (1), effectiveness of positive pressure ventilatory support (15, 25b, 25c, 27, 28, 32), and/or pharma-cological treatments (2,30,33,34). Phase contrast X-ray imaging has shown that this process is initially driven by the transpulmonary pressure that first moves the fluid from the central airways to the lung periphery (10).…”
Section: Introductionmentioning
confidence: 99%